Assessment of Undergraduate Critical Care Nursing Students’ ‘ Knowledge and Attitudes toward Caring of Dying Patients In Colleges of Nursing at Baghdad University - Ahmed F. Hassan1 ,Haider M. Majeed1 , Aqeel H. Jasim2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nurses have played various roles in the development of palliative care, offering leadership, support and focus for the movement. Experiences of death on a clinical placement by nursing students were a major cause of anxiety and sadness. Objectives: To asses of students’ knowledge toward care of dying patient and to find out the relationship between students’ knowledge and their demographical characteristic such as age, gender, post level of education. Methodology: A descriptive study was conducted in the period of December 10th 2018 up to the end of 5th May 2019. A non-probability (purposive) sample of (100) student at college of nursing from different post educational levels, both sexes (males and females), were selected .The data collected was analyzed using SPSS version 17.0. Results: the majority of the study were male who accounted for (58%) of the total participants while female constituted (42%). Most of the study participants (98%) were ages (21-30) years old. (90%) of the student were secondary school graduate. Nanty three percent of the student were married and sixty nine percent were sufficient. Conclusions: The undergraduate critical cares nursing students were adequately prepared to care for terminally ill and dying patients as they had deficiency in some knowledge about palliative care but their knowledge towards palliative care was good.